1972
DOI: 10.1901/jeab.1972.17-127
|View full text |Cite
|
Sign up to set email alerts
|

CONDITIONED SUPPRESSION OF BAR‐PRESSING BEHAVIOR BY STIMULI ASSOCIATED WITH DRUGS1

Abstract: Ten naive male albino rats were trained to press a bar under a variable-interval 30-sec schedule with water as the reinforcer in two experiments. This behavior was disrupted by chlorpromazine in Experiment I (two rats) and by lysergic acid diethylamide (LSD) in both Experiment I (two rats) and Experiment II (six rats). The administration of the drug was paired with an originally neutral white light. After several pairings with either drug, the light also depressed behavior. When the light was no longer paired … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

1972
1972
2007
2007

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 7 publications
1
7
0
Order By: Relevance
“…The 4th day indicates about the same overall level of extinction as the 3rd, but less stability between Ss. This loss of stability after 4-5 trials is consistent with previous findings (Cameron & Appel, 1972). DISCUSSION The data indicate that stimulus generalization to LSD-induced conditioned suppression can occur.…”
Section: Behavioral Proceduressupporting
confidence: 92%
See 1 more Smart Citation
“…The 4th day indicates about the same overall level of extinction as the 3rd, but less stability between Ss. This loss of stability after 4-5 trials is consistent with previous findings (Cameron & Appel, 1972). DISCUSSION The data indicate that stimulus generalization to LSD-induced conditioned suppression can occur.…”
Section: Behavioral Proceduressupporting
confidence: 92%
“…However, it was demonstrated that the "withdrawal syndrome" need not be involved in pharmacologically ind uced conditioned suppression. Injections of amphetamine (Whitney & Trost, 1970), scopolamine (Herrnstein, 1962), and large doses of LSD or chlorpromazine (CPZ) (Cameron & Appel, 1972) have been successfully employed as the USs in CER paradigms. In the LSD-conditioned animals, during the CS, the animals seemed to be "hyperactive" and not at all debilitated, while with CPZ, the animals appeared "poured out" (ataxic?)…”
mentioning
confidence: 99%
“…) is important to avoid confounding due to any direct effects of the drug on performance of the behaviour for which the dependent variables are measured, or on any underlying associative processes. The paradigms to be discussed are: (Cameron and Appel, 1972;Goldberg and Schuster, 1967;Whitney and Trost, 1970) . It has also been demonstrated that many of these drug states can also function as reinforcers (Cappell and Le Blanc, 1973;Pickens and Harris, 1968;Wise, Yokel and de Wit, 1976).…”
Section: B Testing the Aversive Stimulus Properties Of 0-rugsmentioning
confidence: 99%
“…Each Pavlovian session was preceded by a 3D-sec interval, after which the ID-rnin light CS was presented, and an IP injection of 40 mg/kg amobarbital sodium or normal saline was administered 3 min after CS onset to the six drug and six placebo Ss, respectively. The procedure of removing, injecting, and replacing S into the compartment required no more than 20 sec, and was modeled after that descn'bed by Cameron and Appel (1972). The S was removed from the apparatus 30 sec after offset of the I D-min CS and returned to its horne cage .…”
Section: Pavlovian Conditioningmentioning
confidence: 99%